THE ROLE OF INTERACTIVE MARKETING IN ENHANCING CUSTOMER CONFIDENCE / A STUDY AT AL-HAYAT PHARMACEUTICALS - Hassan Daghwi Obaid (Scholar Express Journals, 2025)
The research sought to elucidate the function of interactive marketing in bolstering client trust in Al-Hayat Company. The researcher developed a questionnaire of 12 items to gather primary data from a sample of 30 employees at Al-Hayat Company. Consequently, data were gathered and analysed, and hypotheses were evaluated utilising the Statistical Package for the Social Sciences (SPSS). A variety of statistical approaches were employed to fulfil the study objectives, including Pearson's correlation coefficient analysis and simple regression. Upon analysing the study data and its hypotheses, various outcomes were attained, the most notable of which are: There exists a distinction in delineating the parameters of interactive marketing. Certain research uniquely identified interactive marketing characteristics, however the majority concurred on five specific dimensions. The organization's consumer confidence was ordinary, necessitating an increase to maintain its sustainability. Their clientele. The researcher proposed a series of recommendations, the most significant of which are as follows: The imperative of prioritising client loyalty as a strategic objective rather than merely a requirement. Customers are unable to alter their service providers. The organisation must investigate the facets of client trust, pinpoint deficiencies, and endeavour to rectify and augment them through interactive marketing.
Keywords: Interactive Marketing; Enhancing Customer; Confidence